ANALYSIS OF CONCRETE COMPRESSIVE STRENGTH WITH COCONUT FIBER WASTE AS A PARTIAL REPLACEMENT OF FINE AGGREGATE - ISMAIL; YONAS PRIMA ARGA RUMBYARSO; GALI PRIBADI (CV KULTURA DIGITAL MEDIA, 2024)
Although concrete is less strong in resisting tensile loads, the addition of fibers makes it a more resilient construction material, especially fiber concrete which is abrasion resistant and has better tensile, flexural and compressive strengths. In Indonesia, coconut fibers, which have been used since prehistory as a building material, are now being utilized as an additive in cement, thanks to their advantages in absorbing water and having good tensile strength. The use of coconut fibers not only increases the flexibility and strength of concrete, but also utilizes household waste that is difficult to recycle to create high-quality construction materials that are more durable and less prone to cracking. The results of testing the compressive strength of normal concrete at 28 days showed that without coconut fiber waste, the compressive strength was 440 kN (f´c 24.91 Mpa). With the addition of 5% coconut fibers, the compressive strength dropped to 318 kN (f´c 18 Mpa), and with 10% coconut fibers, to 292 kN (f´c 16.53 Mpa), showing the effect of fibers on the mechanical properties of concrete.